Process monitoring and internet of things feasibility for submerged arc welding: State of art. (2021) - Barot, R.S.; Patel, V.J.
Abstract: Good Quality and higher productivity play important role in manufacturing industries. Delivering improved quality product at reduced price in stiff-cut throat competitive market condition needs optimization of process. Welding is one of basic manufacturing process adopted by many industries for the production work. Weld quality inspection is carried out after welding is performed and product are rejected if defects are identified resulting in to repetition of whole cycle. To study and develop credible diagnosis system for welding On-line quality control in industry is customary of strategies. Sensors located in various region of welding play a significant role in online monitoring for process diagnostics. Experimental investigations will help to map weld quality in early stage with real time monitoring weld temperature, voltage, acoustic etc. with help of sensors placed around welding region. Arc column interface data can be captured using sensor and transferred via controllers displayed on mobile or workstation for live monitoring. In present paper authors have put an attempt to find need of submerged arc welding (SAW) arc column behaviour, its varied effect on weld quality, characterization of defect with sensor signals, methods used for monitoring and techniques to make intelligent welding expert system using Internet of Thing (IoT). Smart manufacturing is demanding change in the path of digitalization revolution. Adoption of Internet of Things (IoT) in the welding imparts assistances to overcome constraint based on adaptive control strategy leading to smart welding. Modern manufacturing environment is increasing reliant on high performance monitoring systems.